2018
DOI: 10.4028/www.scientific.net/kem.777.322
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of SAC305 Lead-Free Powder Prepared by Centrifugal Atomization

Abstract: Centrifugal atomization apparatus was constructed to produce solder alloy powder with high quality. In this work, SAC305 alloy was atomized to study the effects of processing parameters, including atomizer disk surface condition and oxygen content in the atomizer chamber on the mean particle size, size distribution, production yield, and morphology of the produced SAC305 powder. The results showed that the atomizer disk surface coated with tin alloy gave the produced powder with smaller mean size, narrower siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cooling rates between 10 3 and 10 5 K s −1 can be reached using this method [22], thus providing an appropriate range of cooling rates for the generation of Al-based metallic glasses. However, a review of the literature reveals that although there are several works on the centrifugal atomization process [23][24][25], studies on the production of metallic glasses using this technique are not found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling rates between 10 3 and 10 5 K s −1 can be reached using this method [22], thus providing an appropriate range of cooling rates for the generation of Al-based metallic glasses. However, a review of the literature reveals that although there are several works on the centrifugal atomization process [23][24][25], studies on the production of metallic glasses using this technique are not found in the literature.…”
Section: Introductionmentioning
confidence: 99%